Seaweeds of the Greek coasts. II. Ulvophyceae - TSIAMIS, K.; PANAYOTIDIS, P.; ECONOMOU-AMILLI, A.; KATSAROS, C. (Mediterranean Marine Science, 2014)
An updated checklist of the green seaweeds (Ulvophyceae) of the Greek coasts is provided, based on both literature records and new collections. The total number of species and infraspecific taxa currently accepted is 95. The occurrence of each taxon in the North Aegean, South Aegean and Ionian Seas is given. In addition, 12 taxa pending confirmation of their presence, 9 excludenda and 14 inquirenda are briefly discussed.